Effect of polyvinylidene fluoride on the acoustic impedance matching, poling enhancement and piezoelectric properties of 0–3 smart lead-free piezoelectric Portland cement composites - Thanyapon Wittinanon (2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature. Smart composites, which are composed of piezoelectric ceramics and cement-based materials, have been developed for sensing and health monitoring of concrete infrastructure. Barium titanate (BT)-Portland cement (PC)-polyvinylidene fluoride (PVDF) composites with 40-60 vol.% BT particles (with a median size of ~ 425 µm) and 0-7 vol.% PVDF were fabricated by the pressing and curing method. The effects of the PVDF content on the acoustic impedance (Zc), dielectric constant (εr), piezoelectric charge coefficient (d33) and piezoelectric voltage coefficient (g33) of the BT-PC-PVDF composites were investigated. Increasing the PVDF content in the composites led to a decrease in the Zc value so that it approached that of concrete. The PC phase was replaced by the PVDF phase in the BT-cement-based composites to reduce the leakage current in these composites. As a result, the piezoelectric properties of the BT-PC-PVDF composites improved noticeably. BT contents of 50 and 60 vol.% and a PVDF of 5 vol.% had the highest d33~24-25 pC/N. Moreover, the composite with 50 vol.% BT and 5 vol.% PVDF had the highest piezoelectric voltage coefficient herein (g33=14.6 × 10-3 V∙m/N).